1994
DOI: 10.1111/j.1365-313x.1994.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and cDNA sequence of glucose‐6‐phosphate dehydrogenase from potato (Solatium tuberosum L.)

Abstract: Summary Glucose‐6‐phosphate dehydrogenase (G6PDH, E.C. 1.1.1.49) has been purified from potato tuber at least 850‐fold to apparent homogeneity as judged by SDS‐PAGE. The enzyme was characterized by Km values of 260 μM for glucose‐6‐phosphate and 6 μM for NADP and a broad pH optimum between phi 7.5 and 9. NADPH, GTP, ATP, acetyl CoA and CoA inhibited G6PDH activity. Dithiothreitol (DTT) did not inactivate the enzyme. A highly specific antiserum was produced in a rabbit and used for immunodetection of G6PDH in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 25 publications
4
128
0
1
Order By: Relevance
“…It was unequivocally shown that chloroplast/cytosol isoenzymes exist for G6PDH and 6PGDH both in green leaf cells (Schnarrenberger et al, 1973) and in nongreen tissues (Schnarrenberger et al, 1975;Simcox et al, 1977;Simcox and Dennis, 1978;Nishimura and Beevers, 1981). Cytosolic G6PDH has even been cloned from potato tuber (Graeve et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It was unequivocally shown that chloroplast/cytosol isoenzymes exist for G6PDH and 6PGDH both in green leaf cells (Schnarrenberger et al, 1973) and in nongreen tissues (Schnarrenberger et al, 1975;Simcox et al, 1977;Simcox and Dennis, 1978;Nishimura and Beevers, 1981). Cytosolic G6PDH has even been cloned from potato tuber (Graeve et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…G6PDH activity was determined by using a spectrophotometric assay reported previously [21]. The assays were performed at room temperature with a 20 μg extract of cellular protein in a buffer consisting of 0.1 M Tris-HCl (pH 8.5), 0.2 mM NADP and 2 mM glucose-6-phosphate.…”
Section: G6pdh Activity Assaymentioning
confidence: 99%
“…G6PDH activity was measured by exposing identical amounts of cell protein extracts from the wild type and GK-overexpressing H4IIE cell lines, to G6P and NADPH under assay conditions described previously [21]. The NADPH produced per unit assay time is directly proportional to the G6PDH activity.…”
Section: G6pdh Activity Is Higher In the Gk-overexpressing Cell Linesmentioning
confidence: 99%
“…Chloroplastic G6PDH has high homology to the plant cytosolic, animal and yeast enzymes, but contains six specific cysteine residues which are not found in the cytosolic protein, all of them being located in the first third of the amino-acid sequence. These residues are also absent on the cyanobacterial enzyme which contains three cysteine residues located further downstream (Graeve, von Schaewen & Scheibe, 1994;von Schaewen et al, 1995). Nevertheless, the cyanobacterial enzyme appears to be also redox-controlled (Gleason, 1996).…”
Section: {D) Cf^-atpasementioning
confidence: 99%